Estudo e avaliação patológica do bloco de enfermaria no hospital Santa Casa de Campo Mourão-PR – estudo de caso - Andrade, Leonardo Cagliari de (2018)
Pathology is a branch of civil engineering that studies the edification’s problems, seeking out through tests and evaluations to determine the mechanisms that originated the pathologies, and then proposing solutions. This study evaluated the situations of the masonry wall of the Santa Casa Hospital’s nursery ward at Campo Mourão –PR, seeking out to propose quick solutions to revitalize this edification. Through a bibliographical research was possible to determine the classification criteria of the cracks, its forming mechanisms and the processes by which they begin and, finally, determine the techniques that can be used for correction and revitalization. With an inspection and visual analysis of the masonry wall, it was verified a presence of fissures originated by the thermal variation, effects of overloads due to the lack of structural elements in the openings of the masonry and repression. Using the Midpoint rule was determined that the repression’s origin was leaks present in the passageway boxes annexed to the edification. With the aid of the techniques suggested by the bibliographical consulted and regulatory standard, was able to determinate a plan of action for the recovery of the building, consisting of the repair of the passageway boxes, introduction of wick and sill in the wall’s openings, removal of the old layer of mortar sealing, fissure closure and the introduction of reinforced mortar sealing with waterproofing additives. It was concluded that no edification is immune to degradation, on that way, the constant building maintenance is the paramount importance to the user’s safety and comfort. Also is very important that the professionals have in mind that no correct techniques should be done without solving the cracking mechanisms and that the same must be determined with certainty.